النفس عند فخر الدين الرازي - الضاهر سليمان; حريبا لؤي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تشغل مشكلة النفس مكانة مهمة في الفكر الفلسفي لأنها صلة الوصل بين مبحثين رئيسيين في الفلسفة, هما مبحث المعرفة ومبحث الوجود, وقد لقيت اهتماماً كبيراً عبر تاريخ الفكر الإنساني, وذهب الفلاسفة في تفسيرها اتجاهاتٍ مختلفةً ومتباينةً. وقد انعكست هذه المواقف في آراء ونظريات المفكرين والفلاسفة العرب, حيث عالجوا هذه المسألة معالجة عميقة ودقيقة, نابعة من طبيعة موقفهم المتردد بين الديني والعقلي؛ منهم فخر الدين الرازي الذي أفرد لهذه المشكلة مساحة واسعة في مؤلفاته. ولنا هنا أن نتساءل عن حقيقة موقفه؟، وكيف استطاع أن يوفق بين نزعته الفلسفية العقلية وبين المفهوم الإسلامي للنفس, القائم على مسلمات النص؟ The problem of the Self occupies an important place in the philosophical thought, as the link between two major sections in philosophy: the study of knowledge and the study of existence which has received considerable attention throughout the history of human thought. Philosophers have split into several directions notably the physical, the ideal and the realistic. These attitudes reflected in the opinions and theories of Arab thinkers and philosophers where they treated this matter deeply and accurately, stemming from the nature of their hesitant attitude among the religious and the mental, of whom Fakhr al-Deen al-Razi has devoted to this problem a large area in his compositions. We wonder here about the nature of his attitude and how could he reconcile his philosophical mental bias and the Islamic concept of the self which is based on the axioms of the text?